Implementation of Ecological Class Program at SMK Bakti Karya Parigi - Awang Dody Kardeli; Irpan Ilmi; Cepi Budiyanto (Departement of Mathematics Education, 2023)
Ecological-oriented education becomes important when there is an ecological crisis like today. The ecological crisis marked by the relationship between humans and culture with the environment in which they live, live, and exploit natural resources. This is the challenge of education in Indonesia to form and produce citizens who care about environmental damage or pollution while also wanting to preserve and make use of the environment in a balanced way. The method used in this study is a descriptive qualitative method using data collection techniques including interviews, observation, literature review or literature and documentation. The results of this study indicate that Bakti Karya Parigi Vocational School has implemented the Ecology Class program through effective planning, organizing and implementation. Ecology class has been implemented since 2016 with a special ecology class program